2013
DOI: 10.1007/s00431-013-2083-7
|View full text |Cite
|
Sign up to set email alerts
|

Ketoacidosis at presentation of type 1 diabetes mellitus in children: a retrospective 20-year experience from a tertiary care hospital in Serbia

Abstract: The overall frequency of DKA in children with newly diagnosed type 1 diabetes decreased over a 20-year period at our hospital. However, children aged <5 years and adolescents are still at high risk for DKA at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…The non-significant decrease in the proportion of presentations in DKA in our patient population is also similar to the worldwide trends [22]. While decrease in DKA rates have been noted in some countries [22][23][24] many developed countries continue to report high rates [25][26][27]. Factors like degree of awareness of symptoms of diabetes among parents and primary care physicians have been proposed to affect the risk of developing DKA at diagnosis [27] but targeted intervention with a community-based information program, generally considered successful in preventing ketoacidosis [28], failed to decrease the rates of DKA in one study [25].…”
Section: Discussionsupporting
confidence: 81%
“…The non-significant decrease in the proportion of presentations in DKA in our patient population is also similar to the worldwide trends [22]. While decrease in DKA rates have been noted in some countries [22][23][24] many developed countries continue to report high rates [25][26][27]. Factors like degree of awareness of symptoms of diabetes among parents and primary care physicians have been proposed to affect the risk of developing DKA at diagnosis [27] but targeted intervention with a community-based information program, generally considered successful in preventing ketoacidosis [28], failed to decrease the rates of DKA in one study [25].…”
Section: Discussionsupporting
confidence: 81%
“…This is in accordance with other reports of children with new-onset T1DM 3537 and is possibly because of closer supervision by caretakers of younger children. Though we might have expected the older children, who were symptomatic, on average, for almost a month prior to presenting in DKA, to have a more significant degree of acidosis and higher cortisol levels than the younger children, they did not.…”
Section: Discussionsupporting
confidence: 93%
“…The data confirm the results of other studies indicating that age was not significantly associated with the severity of DKA (28)(29)(30). In contrast Jesic et al (31) reported that severe DKA was more frequent in the age group < 5 years.…”
Section: Discussionmentioning
confidence: 83%